Sharia Peer-To-Peer Lending Business Model: Improving Sustainable Msme’s Financing in Indonesia - Afrizal; Muhammad Yafiz; Marliyah (Faculty of Law, Universitas Pekalongan, 2024)
Indonesia is a Muslim-majority country with a large market potential and a Muslim population of 85 percent. However, the number of Sharia fintech companies is still far behind compared to conventional fintech. The government in Indonesia is focusing on the halal economic and financial industry, and the Sharia P2P lending business model is being explored to increase the sustainable growth of MSME financing in the country. This research, qualitative and quantitative, uses the Analytic Network Process (ANP) method to transform primary data from in-depth interviews with experts and practitioners. According to the findings, a Sharia P2P lending business model based on the fintech ecosystem can increase long-term MSME financing by combining regulatory factors, community-based financing products, and the major ecosystem network. A business model that complies with Sharia principles and considers the needs of MSMEs is crucial for ensuring sustainability in financing. It entails developing mechanisms that increase access to MSMEs while adhering to Sharia principles, such as sustainable community-based financing products and Sharia-compliant risk adjustments.